Antioxidant activities of a polyglucuronic acid sodium salt obtained from TEMPO-mediated oxidation of xanthan. (13th February 2015) - Delattre, C.; Pierre, G.; Gardarin, C.; Traikia, M.; Elboutachfaiti, R.; Isogai, A.; Michaud, P.
Highlights: Xanthan was successfully C-6 carboxylated by TEMPO/NaOCl/NaBr media system. A new family of polyglucuronic acid called xanthouronan was generated. Xanthouronan was a high molecular weight polysaccharide with antioxidant properties. Xanthouronan was very resistant to various enzymatic treatments. Abstract: A xanthouronic acid sodium salt called xanthouronan was produced from xanthan by regioselective oxidation with NaOCl/NaBr using 2, 2, 6, 6-tetramethylpiperidine-1-oxy radical (TEMPO) as catalyst. The efficiency of the one pot TEMPO-mediated oxidation was confirmed by HPAEC-PAD, 13 C NMR, and FT-IR. The oxidation degree was close to 98% and the mass yield of this new polyglucuronic acid was higher than 90% (w/w). The macromolecular characterization of xanthouronan using SEC-MALLS showed a molecular size reduced by a third due to the oxidation treatment and the degree of polymerization (DP) of the xanthouronan form was about 665. The evaluation of the enzymatic degradation of this C-6 carboxylated xanthan by various polysaccharide hydrolases and one polysaccharide lyase showed its high resistant to biodegradation. The antioxidant activity of xanthouronan was also tested by using the 2, 2′-diphenyl-1-picrylhydrazyle (DPPH) and hydroxyl radical procedures. At 1 g/L, xanthouronan presented 75% of the ascorbic acid antioxidant activity.